Treatment of Aortoiliac Occlusive Disease With the Covered Endovascular Reconstruction of the Aortic Bifurcation (CERAB) Technique: Results of a UK Multicenter Study. (October 2021) - Saratzis, Athanasios; Salem, Murtaza; Sabbagh, Cezar; Abisi, Said; Huasen, Bella; Egun, Ansy; Nash, Jennifer; Lau, Pui Fong; Chaudhuri, Arindam; Dey, Ramita; Patrone, Lorenzo; Malina, Martin; et al.
Objective: This UK multicenter study aims to report early- and medium-term results following covered endovascular reconstruction of aortic bifurcation (CERAB) for the treatment of aortoiliac occlusive disease (AIOD) in patients with chronic limb threatening ischemia (CLTI) or intermittent claudication (IC). Materials and Methods: Retrospective case analysis was performed of patients who underwent CERAB between November 1, 2012 and March 31, 2020 in 6 centers across the United Kingdom. Anatomical data, including degree of plaque calcification, were assessed using preoperative imaging. Outcome measures included mortality, perioperative complications, target lesion reintervention (TLR), and major limb amputation. Primary, assisted primary, and secondary patencies were calculated at set intervals. Results: A total of 116 patients underwent CERAB over the study period for the following reasons [48% presenting with CLTI (Rutherford 4–6) and 52% with IC (Rutherford 1–3)]; 82% presented had Trans-Atlantic Inter-Society Consensus (TASC) D AIOD disease. Median age was 65 years (range 42–90 years); 76% of the cohort were male. Severely calcified aortic and iliac lesions were noted in 90% and 80% of patients, respectively. Over a median follow-up of 18 months (range 1–91 months), 2 (1.7%) patients were lost to follow up. In total 5, (4.3%) patients died and 2 (1.7%) had a major amputation. Endovascular TLR was required in 14 (12.1%) patients at last follow up. Surgical TLR was performed in 4 (3.4%) patients at last follow-up. Seven (6%) patients developed an aortic/iliac stent occlusion at last follow-up. The Kaplan-Meier (KM) freedom from TLR at 1 year was 94% and KM 1-year primary patency, assisted primary patency, and secondary patency were 88%, 94%, and 98% respectively. Subanalysis found the following features were associated with need for TLR; TASC D disease (OR = 2.45, 95% CI 1.44 to 3.71), severe aortic calcification (OR = 2.01, 95% CI 1.03 to 2.20), and presence of tissue loss at baseline (OR = 1.43, 95% CI 1.01 to 4.63). Conclusion: Perioperative (<30 days) and medium-term morbidity, mortality, and patency rates in this pragmatic cohort of patients with severe AIOD lesions show that CERAB is a valid revascularization option. A direct comparison with surgical treatments for AIOD in a randomized controlled trial is justified.